CISSP Training Kit - Miller, David R.; Pearson, Brock; Oriyano, Sean-Philip (Microsoft Press, 2014)
Annotation
Keywords: Electronic data processing personnel -- Study guides -- Certification; Computer networks -- Study guides -- Security measures -- Examinations; Electronic Data Processing Personnel; Certification; Computer Networks; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Electronic data processing personnel; Certification; Study guides